Empowerment and incapacitation - on institutional framing of a technical stadardised understanding of healthiness and its role for the narrative subjectivization - Wiegerling Klaus (Filozofija i Društvo, 2015)
With the help of the discourse on healthiness in times of a demographic change it is shown how subjectivization in the institutions of biopolitics like healthcare takes place. In the light of new technical capacities, in which biotechnology and information technology converge, the role of processes of standardization and the experience of suffering for subjectivization is exposed. Subjectivization appears not in the manner of a philosophical struggle for concepts, but in a narrative articulation of an experience of difference. The human being is - to say it with Wilhelm Schapp - entangled in stories which run contrary to general and typological concepts. These stories are articulations of deviation and the contrary. The singularity of the own existence and its dignity becomes clear in understanding the difference between the common conception of man and the self-concept. The discussion is developed in four questions: 1) How we can define healthiness in times of transformation the historically mediated and in the first-person-view given human ‘Leib’ to a body, which is given in a third-person-view? 2) How we can catch the change of our understanding of healthiness in the light of new technical possibilities which enhance our physical capacities? 3) Which metaphysics - as an unarticulated presupposition -manifests behind this change? 4) Which role plays this metaphysics in the institutions of biopolitics?